Multielement Imaging Reveals the Diagenetic Features and Varied Water Redox Conditions of a Lacustrine Dolomite Nodule. (10th January 2022) - Liu, Yuke; He, Wenyuan; Zhang, Jinyou; Liu, Zhenwu; Chen, Fazi; Wang, Huajian; Ye, Yuntao; Lyu, Yitong; Gao, Zhiyong; Yu, Zhichao; Bi, Lina; Zhang, Shuichang
Abstract : The genesis of dolostone has long been puzzling for more than two centuries. Although much work has been done on investigating the process of dolomitization, little emphasis has been put on examining the diagenetic water redox condition with the wealthy geochemical information preserved in primary dolomite, which is believed to archive the aqueous environment as well as biotic and/or abiotic effects during formation. In situ interpretation with high resolution is a prerequisite in refined research of dolomite. Here, we reported the multielement imaging results of a lacustrine dolomite nodule with the host black shale from the Songliao Basin, northeast of China. Micro X-ray fluorescence ( μ -XRF) with a spatial resolution down to 10 μ m was used for in situ scanning. Two key parameter settings of the μ -XRF, including single-point exposure time and spatial resolution, were optimized to achieve a better result in a reasonable scanning time scale. The final imaging data graphically revealed dynamic variation of elemental distributions, including elements enriched in dolomite (e.g., Ca, Mg, Fe, and Mn), clastic quartz (Si), and clay minerals (e.g., Al and K) and redox-sensitive trace elements (e.g., Cr, Mo, V, and U). The well-preserved laminated structures inside the nodule and the features with a magnesium-rich core wrapped with an iron-concentric outer layer and a manganese-concentric shell together indicated its primary form as dolomite and a gradual transformation into ankerite as well as manganese-ankerite. The elemental variation indicates a varied bottom water redox condition, which involved from sulfidic to ferruginous and manganous zones. Here, we propose that the intermittent supplies of sulfate and Fe-/Mn-oxidized minerals interrupting the black shale deposition while favoring dolomitization might be brought by the oxidized and salted seawater. And this lacustrine dolomite is expected to be a potential fingerprint mineral in tracking the seawater intrusions to the Songliao Basin which happened 91 million years ago.